Effect of different salt additions on the taste and flavor-related compounds in chicken soup - Jia, Rong; Yin, Xiaoyan; Yang, Yucai; Liao, Guozhou; Gu, Dahai; Pu, Yuehong; Wang, Guiying (Frontiers in Nutrition, 2024)
Chicken soup is popular among consumers because of its delicious taste, strong flavor, and abundant nutritional value. Twenty-four Yunnan local hens were stewed by adding different amounts of NaCl (1.5%, 2%, 2.5%, 3%, m/m, calculated based on chicken carcass weight; chicken: water = 1:2 (m/m)) to study the effect of salt addition on taste-and flavor-related compounds in chicken soup. Sensory evaluation results showed that the 2% and 2.5% NaCl treatment groups had higher scores. Water-soluble small molecule compounds were detected by LC-Q/TOF-MS based metabolomics approach, among which amino acids and their derivatives, nucleic acids, and small peptides were the main components. The concentration of Water-soluble small molecule substances in chicken soup samples with different salt additions showed a clear trend of separation and reached the highest in the 2.5% NaCl treatment group. Volatile flavor compounds in the chicken soup were analyzed by HS-SPME-GC-MS, including aldehydes, and alcohols, and the relative concentration of flavor compounds in the 2.5% salt treatment group was the highest. In summary, the addition of salt could improve the overall flavor of chicken broth, and the optimal salt addition of NaCl in chicken soup is 2.5%.